General practitioners’ perspectives on campaigns to promote rapid help-seeking behaviour at the onset of rheumatoid arthritis - Stack, Rebecca J. (Informa Healthcare, 2014)
Objective. To explore general practitioners’ (GPs’) perspectives on public health campaigns to encourage people with the early symptoms of rheumatoid arthritis (RA) to seek medical help rapidly. Design. Nineteen GPs participated in four semi-structured focus groups. Focus groups were audio-recorded, transcribed verbatim, and analysed using thematic analysis. Results. GPs recognised the need for the early treatment of RA and identified that facilitating appropriate access to care was important. However, not all held the view that a delay in help seeking was a clinically significant issue. Furthermore, many were concerned that the early symptoms of RA were often non-specific, and that current knowledge about the nature of symptoms at disease onset was inadequate to inform the content of a help-seeking campaign. They argued that a campaign might not be able to specifically target those who need to present urgently. Poorly designed campaigns were suggested to have a negative impact on GPs’ workloads, and would “clog up” the referral pathway for genuine cases of RA. Conclusions. GPs were supportive of strategies to improve access to Rheumatological care and increase public awareness of RA symptoms. However, they have identified important issues that need to be considered in developing a public health campaign that forms part of an overall strategy to reduce time to treatment for patients with new onset RA. This study highlights the value of gaining GPs’ perspectives before launching health promotion campaigns.